Digital Reproductive Health Literacy for a Couples: Understanding of Sexually Transmitted Infections and Reproductive Tract Infections - Inayatul Aini; Dwi Anik Karya Setiarini; Ruliati Ruliati; Nurul Azmi Arfan; Rizka Firdausi Nuzula (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to obtain a theoretical overview of how the tendency of couples to obtain information about sexually transmitted infections and reproductive tract infections. The review will focus on literature sources that have previously examined how the use of digital media as a source of knowledge to recognize sexually transmitted infections and reproductive tract infections. The research method in this study is a discourse search and analysis with a content analysis approach of a scientific work. The study will be described with a narrative that has been qualitatively analysis based on certain categories. Data sources are various scientific journals, reference books and other sources considered compatible with this study. The results of the study found that digital media became an alternative medium for accessing information. Knowledge about Sexually Transmitted Infections (STIs) and Reproductive Tract Infections (RTIs), is needed for newlywed couples, so that they have a reference for sexual behaviour. Good sex is sex that is done with a legal partner and guaranteed health, all of which information can be accessed through increasingly widespread digital media